Prácticas culturales: dos colectivos de migrantes, dos países de destino (2012)
This article aims to analyze the social and cultural practices of two groups of migrants in two Latin American countries: the case of Argentine immigrants in Chile, and Senegalese immigrants in Argentina. We understand that these practices have as background the meeting between compatriots, and that they appeal to the creativity and spontaneity in the context of integration into the host society, helping to form networks and social ties that perhaps did not exist before. These creative and re-creative activities contribute to the (re) configuration of national identity in a context of migration. At the same time, they have in common that they arise spontaneously without advance planning. They also are setting up a network of relationships that nurture both the “Argentinian” and the “Senegalese identity” in the immigration context of reception.Keywords: Cultural practices, Argentinean migration, Senegalese migration, integration.